The effectiveness of raising Hong Kong parents' awareness of antimicrobial resistance through an education program with peer support on social media: a randomized, controlled pilot study - Pui-Lai Or; Tai-Yin Ching (BMC, 2022)
Abstract Background The aim of this study was to address the misuse of antibiotics and test the feasibility of an education program with peer support on social media in improving parents' knowledge on antimicrobial resistance at a regional level in Hong Kong. This pilot, if successful, will be developed into a main study. Methods A cluster randomized controlled trial with two-arms were implemented. The intervention program consisted of two weekly sessions and each session lasted for 90 min. Parents in the intervention group would join a Facebook Page of Antibiotic Use, this online platform would allow participants to build a social network. A total of 48 parents had participated in the program. Parental knowledge and attitude were measured before and after the program using the Parental Perception on Antibiotics (PAPA) scale and the General Self-Efficacy Scale (GSE) to assess differences between and within the intervention and control groups. Results All parents in the intervention group had an understanding that antibiotics could be effective at treating some infections only, as compared to 40% in the control group. All parents in the intervention group and 85% of the control group disagreed that they should reduce the dose of antibiotics when their children were recovering. The test was statistically significant (p = 0.039) at p < 0.05. There were a significant difference and a strong negative correlation between peer support on Facebook and the parents' belief that antibiotics could be stopped when their children felt better, with Pearson coefficient of − 0.78 at p < 0.001. In general, there was no significant difference between the two groups with respect to the scale. Conclusions Based on the findings in this pilot study, a further study focused on the education program with enhancement and peer support should be implemented on a larger scale with considerations of how it might support reducing incidence of antimicrobial resistance and potentially influencing prescription expectations of patients when seeking healthcare. Trial registration Retrospectively registered Chinese Clinical Trial Registry ChiCTR2100044870 . Registered on 31 March 2021.